2007
DOI: 10.17660/actahortic.2007.739.53
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iso Method in Saffron Qualification

Abstract: The factors which are very important in saffron are crocin (color), picrocrocin (flavor) and safranal (aroma). Higher amount of these compounds in saffron provide higher quality of saffron. ISO (the international organization for standardization) has set a classification of saffron based on minimum requirements of each quality. According to ISO picrocrocin, safranal and crocin are expressed as direct reading of the absorbance of 1 % aqueous solution of dried saffron at 257, 330 and 440 nm respectively. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…On performing amperometric titration between crocin and cysteine, the end point indicated a crocin to cysteine ratio of 1:2.The above amperometric titration procedure was used to determine the concentration of crocin in a sample of saffron. The concentration of crocin in saffron was found to be 2.13%.This is in good agreement with the HPLC analysis as determined by earlier workers [11][12][13]16 . The purity of isolated crocin was found to be 96.81%.Some experiments were carried out on recovery and the percentage recovery varied from 98.56 to 100.31%.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…On performing amperometric titration between crocin and cysteine, the end point indicated a crocin to cysteine ratio of 1:2.The above amperometric titration procedure was used to determine the concentration of crocin in a sample of saffron. The concentration of crocin in saffron was found to be 2.13%.This is in good agreement with the HPLC analysis as determined by earlier workers [11][12][13]16 . The purity of isolated crocin was found to be 96.81%.Some experiments were carried out on recovery and the percentage recovery varied from 98.56 to 100.31%.…”
Section: Resultssupporting
confidence: 90%
“…It means crocin must be a good anti depressant. Chemically it is (β, β 'digentiobiosyl 8, Crocin has been determined earlier in Crocus sativus 11,12 and Gardenia Jasmenoides Ellis 4,13 using some analytical techniques. Though, the use of polarographic and voltammetric methods have been widely done for the analysis of organic compounds in samples of natural origin 14,15 but, crocin being polarographically inactive could not be analyzed using this electrochemical method.…”
Section: Introductionmentioning
confidence: 99%
“…We have observed that the good amount of crocin and safranal obtained in the extract of methanol and water gradient (50:50). However, on the basis of concentration used for methanol and water, the performed chromatographic method conducted a good separation and resolution of the sample components, better than other proposed gradient conditions reported previously [11,[17][18].…”
Section: Resultsmentioning
confidence: 70%
“…For this purpose, the absorbance of 1% aqueous solution of dried saffron samples was measured at 257 and 440 nm wavelength. Even though this method is also suggested to determine aroma strength, it was not preferred since it was stated in other studies that presented safranal in aqueous solution could interfere with absorbance of crocetin esters (mainly cis-isomers) at suggested wavelength of 330 nm in ISO 3632 (2011) spectrophotometric measurement technique (García-Rodríguez et al, 2017;Hadizadeh et al, 2006;Carmona et al, 2006b). (Heidarbeigi et al, 2015).…”
Section: Saffron Materialsmentioning
confidence: 99%